2016
DOI: 10.1093/mnras/stw638
|View full text |Cite
|
Sign up to set email alerts
|

FR II radio galaxies at low frequencies – I. Morphology, magnetic field strength and energetics

Abstract: Due to their steep spectra, low-frequency observations of Fanaroff-Riley type II (FR II) radio galaxies potentially provide key insights in to the morphology, energetics and spectrum of these powerful radio sources. However, limitations imposed by the previous generation of radio interferometers at metre wavelengths have meant that this region of parameter space remains largely unexplored. In this paper, the first in a series examining FR IIs at low frequencies, we use LOFAR (LOw Frequency ARray) observations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 76 publications
(140 reference statements)
9
66
0
Order By: Relevance
“…Hence, it is uncertain how accurately we can determine the injection spectral index. In any case, within the stated errors, the injection index is in approximate agreement with studies of active radio galaxies (Harwood et al 2015(Harwood et al , 2016. Furthermore, simulations suggest (Kapinska et al 2015) that the observed integrated spectrum can steepen owing to mixing of electron populations.…”
Section: Discussionsupporting
confidence: 85%
“…Hence, it is uncertain how accurately we can determine the injection spectral index. In any case, within the stated errors, the injection index is in approximate agreement with studies of active radio galaxies (Harwood et al 2015(Harwood et al , 2016. Furthermore, simulations suggest (Kapinska et al 2015) that the observed integrated spectrum can steepen owing to mixing of electron populations.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, in determining the physical parameters of the two radio lobes in G29.37+0.1 we used an intermediate spectral index ∼0.5, a compromise between the values measured between 610 and 1400 MHz in both features. Firstly, we found that similar values of the equipartition magnetic field and energy density were reported in the literature for other FRII radio galaxies also observed with GMRT (Harwood et al 2016), as well as for a sample of giant radio galaxies . Considering a smaller value for K 0 yields magnetic fields up to three times smaller than those computed assuming dominance of protons (K 0 1).…”
Section: Extragalactic Emission From G2937+01?supporting
confidence: 87%
“…Several previously published works have noted such a discrepancy (corresponding to B (0.3-2.5)B eq , e.g. Wilson et al 2001;Grandi et al 2003;Harwood et al 2016) in the lobes of radio galaxies from which the IC X-rays are detected. It is noteworthy that none of the previously published comparisons show differences as significant as that we have found.…”
Section: X-ray Associated With the Radio-lobes In G2937+01?mentioning
confidence: 92%
“…The LOFAR studies of individual active (e.g. Orrù et al 2015;Harwood et al 2016;Heesen et al 2016) and remnant (Shulevski et al 2015b;Brienza et al 2016) radio galaxies have already expanded our understanding of radio galaxies at low frequencies, but studies of the larger sample of sources that we have imaged will provide the opportunity to determine the applicability of these findings to the population as a whole.…”
Section: Scientific Potentialmentioning
confidence: 99%
“…Although ionospheric and beam effects hinder the image fidelity of these preliminary images, we are able to image data from baselines shorter than 12 kλ to produce 25 resolution images that typically have a noise level of 200-500 µJy/beam away from bright sources. Such sensitive, low-frequency images have not previously been produced over such a wide area and are sufficient to accomplish many of the scientific objectives of the survey (see Brienza et al 2016;Harwood et al 2016;Heesen et al 2016;Mahony et al 2016;Shulevski et al 2015a,b for examples).…”
Section: Introductionmentioning
confidence: 99%